AN ECONOMIC ANALYSIS OF SOME FACTORS AFFECTING IN MARKETING EFFICIENCY OF DRY ONION CROP USING THE TOBIT REGRESSION MODEL - Jassam, Q. T.; Abd Al-majeed , A. T.; Ali, E. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The study was aimed to evaluate the marketing efficiency of dry Onion crop in Salah al-Deen, as estimate the impact of some quality and quantity factors in the efficiency of marketing process of crop using Tobit regression model. The average marketing efficiency of the research sample was 71.3686%. The marketing margins differed according to the marketing channel followed in marketing the crop. The qualitative and quantitative variables in the model are productivity, family size, distance from the market, educational level. The estimated model revealed that a variable productivity is the most important and influential in marketing efficiency, followed by the variable of the distance between the farm and the market, then the variables of family size and educational level, with less influence according to the estimated model values. The Wald statistical test, which follows the chi-square distribution at degree of freedom d.f4, revealed the significant values of the traits of Tobit regression model as a whole 0.0017 <0.05, this means the independent variables included in the model have a statistically significant effect to predict the value of the qualitative dependent variable. The researchers according to the average value of marketing efficiency has concluded the possibility to raise the value of marketing efficiency by 29.36% in the case of efficient use of resources in the marketing process, as well as the difference in the value of the influence of quantitative and qualitative independent factors on marketing efficiency according to the values ​​of their traits, and the increasment in marketing margins according to the different marketing channels followed in marketing the crop. The research recommended the need to work on increase the marketing efficiency and reducing the high marketing margins received by intermediary agents, with need provide marketing services greater than these intermediaries.